Hemobilia immediately after transcatheter arterial chemoembolization using drug‐eluting beads for hepatocellular carcinoma with intrahepatic bile duct invasion. Issue 4 (22nd November 2017) - Nishi, Maiko; Saeki, Issei; Yamasaki, Takahiro; Maeda, Masaki; Hisanaga, Takuro; Iwamoto, Takuya; Matsumoto, Toshihiko; Hidaka, Isao; Ishikawa, Tsuyoshi; Takami, Taro; Sakaida, Isao
Abstract : Transcatheter arterial chemoembolization (TACE) is used as a palliative treatment for unresectable hepatocellular carcinoma (HCC) worldwide. Recently, a novel drug delivery–embolic agent, the drug‐eluting bead (DEB), was introduced for TACE. There are a few reports of tumor hemorrhage after TACE using DEB (DEB‐TACE) for HCC. However, there have not been any reports of hemobilia immediately after DEB‐TACE for HCC with intrahepatic bile duct invasion. Here, the first such case is reported. A 71‐year‐old woman was admitted to our hospital to undergo DEB‐TACE for multiple HCCs with worsening left intrahepatic bile duct dilatation. She was diagnosed with HCC that extensively invaded the left hepatic duct. After DEB‐TACE through the left hepatic artery, a hepatic arteriogram showed extra flow of the contrast agent to the left hepatic and common bile ducts. Therefore, transcatheter arterial embolization (TAE) of the responsible vessel was carried out using coils, and no extra flow of the contrast agent was identified. The patient was discharged 14 days after TAE without deterioration of liver function. Although hemobilia immediately after DEB‐TACE is rare, there may be increased potential for hemobilia when DEB‐TACE is carried out for HCC with extensive bile duct invasion. We suggest that DEB‐TACE may be contraindicated for such cases.